2013
DOI: 10.3758/s13423-013-0396-1
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in speakers’ perspective taking: The roles of executive control and working memory

Abstract: Both speaking and listening require taking into account the perspective of one's communicative partner. Is perspective taking a domain-specific process internal to the language production and comprehension systems? Or, is perspective taking a domain-general process regulated by the same mechanisms that are used to regulate other forms of behavior? Past research shows listeners' perspective taking is at least partially regulated by inhibitory control and working memory (WM), suggesting that it may be best thoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
123
4
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(136 citation statements)
references
References 31 publications
2
123
4
1
Order By: Relevance
“…shown that children learn to avoid ambiguity from precise (caregiver) feedback (Abbot-Smith et al, 2016;Bacso & Nilsen, 2017;Matthews et al, 2007;Wardlow & Heyman, 2016), so even within the course of a single experiment that includes feedback and/or modeling, increased rates of informativeness can emerge, mediated by executive function skills. Such a paradigm could produce a rather different picture with regard to the link between contrast fixations and informativeness.…”
Section: Discussionmentioning
confidence: 99%
“…shown that children learn to avoid ambiguity from precise (caregiver) feedback (Abbot-Smith et al, 2016;Bacso & Nilsen, 2017;Matthews et al, 2007;Wardlow & Heyman, 2016), so even within the course of a single experiment that includes feedback and/or modeling, increased rates of informativeness can emerge, mediated by executive function skills. Such a paradigm could produce a rather different picture with regard to the link between contrast fixations and informativeness.…”
Section: Discussionmentioning
confidence: 99%
“…In children, Nilsen and Graham (2009) found that during comprehension, 4-5-year-olds' tendency to grab or look at the referential competitor that was hidden from the speaker and hence could not be the speaker's intended referent was related to lower inhibition (see also Brown-Schmidt, 2009, who also showed that the lower inhibitory control, the higher likelihood of egocentric eye-gaze in adults), though they showed no evidence that inhibition affects the production of size adjectives. Wardlow (2013) found that young adults with higher executive functions and working memory were less likely to use perspectiveinappropriate adjectives in the privileged context.…”
Section: Audience Design In Children 28mentioning
confidence: 96%
“…In a study with college students, Wardlow (2013) reported that higher working memory scores meant that indvidiuals had more cognitive resources to allocate towards infering perspective differences in their conversational partner and intergrating that information with their behavior to guide their language use. Working memory is especially critical when the information is considered as privledged ground (knowledge known by one conversational partner) rather than common ground (shared knolwedge), as the listener has to recruit these cognitive resources in order to consider what to divulge and what to keep hidden (see also Lin, Keysar, & Epley, 2010; for additional support for the role of working memory in perspective taking).…”
Section: Discussionmentioning
confidence: 99%